Role of Artificial Intelligence in Talent Management in Learning Organisation: An Empirical Study - Simranjeet Kaur Bagga (Journal of Informatics Education and Research, 2025)
The way traditional human resource management (HRM) is carried out in domestic and international organizations is changing because of artificial intelligence (AI). AI applications have become widely used in human resources management, controlling personnel, influencing recruitment, accounting allocation of resources, and the process by which decisions are made. In the past ten years, HRM has been affected by AI through the automation of functions such as hiring, performance appraisal, and workforce planning. The research on AI in HRM is relatively fragmented and not systematic. In particular, there is a need for a thorough analysis of AI's role within multinational enterprises -for instance, enterprise-wide technology adoption varies by region. At present, AI plays a role in recruitment, because of the need for skilled employees to support economic growth, organizations constantly recruit, and recruitment functions are highly mobile. In particular, in the technology sector, companies use AI and machine learning (ML) tools to improve talent acquisition. Autonomous testing and self-learning algorithms figure into identifying, evaluating, and retaining candidates. The use of AI in HRM raises questions about efficiency, fairness, and decision-making. A sample of 219 people from learning organization were surveyed to know the factors that determines different Role of Artificial Intelligence in Talent Management in Learning Organisation and found that Talent acquisition and recruitment, Workforce Planning & Retention, Performance Management and Biasness are the factors showing role of AI in talent management.